Analysis of User Acceptance Levels of the e-Rapor System Users in Junior High Schools in Rembang District Using The TAM 3 And DeLone & McLean - Yogiana Marta Dewi; Kholiq Budiman (Universitas Negeri Semarang, 2024)
Education is a human right that is important for nation development. Entering the 21st century, education must adapt to digital technology. One important innovation is the e-Report system, a web-based student grade processing application introduced by the Ministry of Education and Culture in 2017. This research aims to analyze the level of user acceptance of the e-Report system in Rembang. Regency Middle School uses the Technology Acceptance Model (TAM) 3 method and the DeLone & McLean method. This research used a quantitative approach by distributing questionnaires to teachers in four junior high schools in Rembang Regency involving 93 samples from a total of 1,201 teachers. The number of samples was calculated using the Slovin formula with a significance error level of 10%. The results of the analysis show that perceived ease of use and perceived usefulness have a significant influence on the acceptance of e-Report technology. Factors such as information quality, self-efficacy, and perceived enjoyment also influence the perceived ease and usefulness of using e-Reports. However, system quality and service quality do not show a significant influence on the acceptance of this technology. This research provides important insights into the factors that influence the acceptance and success of implementing e-Report systems in junior high schools. It is hoped that the research results can become a reference for policy makers in improving administrative efficiency and supporting the learning process through modern technology